ROADS OF THE LOCAL HISTORY IN SAN RAMÓN - Castro Sánchez, Silvia (2014)
This article reviews the ways in which the county of San Ramón’s history has been written since 1917 until 2009.The discussion of the styles used in these histories is organized chronologically in three periods. The author focuses on the ways academic local historians present their works versus the ways local historians ‘by choice’, that is, nonacademic local historians write their books. Some reflections on how to strengthen local history studies in San Ramón are included. In spite of all the works that have been published, San Ramón’s past is still known in a fragmentary fashion.